Effective Mechanisms of State Support for Small and Private Enterprises - Maripova Shahlo Akramovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
To date, a comprehensive work is being carried out in the country to develop and support small and private businesses by the state. The article pays special attention to such issues as current benefits and reforms provided by the state for the development of small and private businesses, credit support for small businesses, the role of the State Fund in the development of the business environment in the country, as well as the study of the current economic status of Uzbekistan in the global market.